Police leaders as thinkers - Verma, Arvind; Das, Dilip K. (Springer, 2023)
This book identifies police leaders who have stood out and chalked a path that has transformed their organizations. It describes these thinkers, who look deep into the challenges of policing and comment critically upon various responses and actions. Featuring profiles of police leaders from various countries, this book features officers with an aptitude for learning, presenting the situations they have confronted and the methods they have adopted to change systems and usher reforms. It identifies the characteristics of thinking police officers, and suggests the ways in which the serious policing challenges of modern times can be addressed by creative and outside the box thinking by leadership. Appropriate for students of criminal justice and policing, for researchers studying law enforcement and for practitioners discussing policing reform, this book will initiate a new debate about the nature and possibilities of building new police for the 21st century.